A methodology for recycling waste expanded polystyrene using flower essential oils. (1st January 2022) - Gil-Jasso, Nadia D.; Giles-Mazón, Edwin A.; Soriano-Giles, Gabriela; Reinheimer, Eric W.; Varela-Guerrero, Víctor; Ballesteros-Rivas, María F.
Graphical abstract: Highlights: Dissolution of waste expanded polystyrene was achieved with flower essential oil. Original material and natural solvents can be recovered and reused. A cheap and green method of EPS recover. Abstract: While polystyrene polymers see broad usage in homes as well as various industrial sectors, their generation of pollutants and disposal remain issues yet to be fully addressed. Expanded polystyrene is commonly used as an insulator and industrial packaging material due to its properties, but the lack of benign, efficient, and economically viable recycling and disposal methodologies to address the global volume of waste material generated has become problematic. Herein, we present an environmentally friendly methodology to recycle waste expanded polystyrene. As an alternative to toxic solvents, essential oils found in flowers are used to dissolve waste expanded polystyrene for purposes of recycling. Characterizations of the polystyrene (both pre -and post -recovery), essential oils, and the dissolutions were performed using infrared spectroscopy, X-ray powder diffraction, thermal gravimetric analysis (TGA), differential scanning calorimetry (DSC), and scanning electron spectroscopy. The results demonstrate that these flower-based essential oils function well as safer alternatives to treat waste expanded polystyrene.